1976
DOI: 10.2136/sssaj1976.03615995004000020018x
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification Kinetics in Soil Systems: The Significance of Good Fits of Data to Mathematical Forms

Abstract: The loss of NO3‐ added to two central Illinois soils was determined in experiments in which the soils were incubated under waterlogged conditions. The loss was measured as a function of substrate concentration in one experiment in which samples were incubated for a single time (24 hours) and as a function of time in a second experiment in which the concentration of the added NO3‐ was held constant (200 ppm NO3‐‐N). The rate of loss of NO3‐ was about 5.5 times higher in one of the soils than in the other. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…3 illustrates the close match of the theory to the plant decomposition data of Jenkinson (9). The model also gives a precise fit to the soil denitrification data of Kohl et al (10) (Fig. 4).…”
Section: Introductionsupporting
confidence: 58%
“…3 illustrates the close match of the theory to the plant decomposition data of Jenkinson (9). The model also gives a precise fit to the soil denitrification data of Kohl et al (10) (Fig. 4).…”
Section: Introductionsupporting
confidence: 58%
“…Moore and Schroeder (1971) reported a Km value of 0.1 /lg N/ml in sewage low in carbon (chemical oxygen demand of 7.5 /lg/ml), while Bowman and Focht reported a value of 170 /lg N/ml in soils amended with 0.6 % glucose-C. Similarly, Kohl et al (1976) showed a difference between soil under 12 yr ofbromegrass (Vrnax = 77.7 /lg N/mljday, Km = 9.6 /lg N/ml) and soil under a yearly corn-soybean rotation (Vrnax = 48.7 /lg N/mljday, Km = 4.1 /lg N/ml), which they attributed to differences in the available carbon between the two soils, even though both were amended with glucose. Without glucose, there were 312 and 1467% decreases in the denitrification rates of the soils under bromegrass and corn-soybean rotation, respectively.…”
Section: Substrates and Productsmentioning
confidence: 97%
“…These investigators were unable to determine the Km because the process was catalyzed by soil organic matter, and they had no effective way of measuring the available carbon concentration, unlike Bowman and Focht (1974), who added measured levels of glucose to a soil having a low indigenous "background carbon" content. Kohl et al (1976) showed that Bowman and Focht's (1974) data could also be fitted to a series of nonlinear differential equations that were derived from the kinetics of a more complex reaction sequence that assumed a limitation of reductant (available carbon) at the primary dehydrogenase level.…”
Section: Substrates and Productsmentioning
confidence: 99%
“…Although microbial effects relative to C : N ratios of waste were not evaluated in this study, it is well established VFAs present in swine waste stimulate microbes, consequently depleting soil O 2 and increasing denitrification rates (Nommik 1956;Bremner and Shaw 1958;Ready, Rao, and Jessup 1982;Paul and Beauchamp 1989;Papendick and Campbell 1980). As C becomes increasingly available, N becomes the ratelimiting nutrient in denitrification (Kohl et al 1976), thus availability of N over time may explain some temporal variation.…”
Section: Resultsmentioning
confidence: 99%